2021
DOI: 10.3389/fonc.2021.709036
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia With TCF3-ZNF384 Rearrangement as a Distinct Subtype of Disease With Distinct Treatments: Perspectives From A Case Report and Literature Review

Abstract: BackgroundZNF384 rearrangements are found in 5-10% of B-cell acute lymphoblastic leukemia (B-ALL) and 48% of B cell/myeloid mixed phenotype acute leukemia (B/M MPAL). ZNF384-rearranged B-ALL is prone to lineage conversion after chemotherapy. TCF3 is the second most common rearrangement partner of ZNF384 in B-ALL (27.5%) and the most common partner in B/M MPAL (53.3%). TCF3-ZNF384 fusion is related to a poor steroid response and a high frequency of relapse. It is mostly reported in children and adolescents but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…The transactivation domain of TCF3 and the coding region of ZNF384 were well reserved. 59 Gene set enrichment analysis (GSEA) showed that the genes regulated by TCF3-ZNF384 are involved in hematopoietic stem cell features. Most cases of TCF3-ZNF384 ALLs have additional alterations driving the RAS signaling pathway genes and CDKN2A/B deletion in patients with B-ALL harboring TCF3-ZNF384 .…”
Section: Introductionmentioning
confidence: 99%
“…The transactivation domain of TCF3 and the coding region of ZNF384 were well reserved. 59 Gene set enrichment analysis (GSEA) showed that the genes regulated by TCF3-ZNF384 are involved in hematopoietic stem cell features. Most cases of TCF3-ZNF384 ALLs have additional alterations driving the RAS signaling pathway genes and CDKN2A/B deletion in patients with B-ALL harboring TCF3-ZNF384 .…”
Section: Introductionmentioning
confidence: 99%